2022
DOI: 10.3389/fimmu.2022.902853
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activities of Interleukin-27: A Partner for Interferons?

Abstract: Emergence of new, pandemic-level viral threats has brought to the forefront the importance of viral immunology and continued improvement of antiviral therapies. Interleukin-27 (IL-27) is a pleiotropic cytokine that regulates both innate and adaptive immune responses. Accumulating evidence has revealed potent antiviral activities of IL-27 against numerous viruses, including HIV, influenza, HBV and more. IL-27 contributes to the immune response against viruses indirectly by increasing production of interferons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 107 publications
0
16
0
Order By: Relevance
“…IL-27 is an anti-inflammatory cytokine that activates Th1 cells and natural killer cells, inhibits Th2 and Th17 cells, and stimulates release of IL-10 by T cells, and has been reported as a reliable predictor of adverse outcomes and mortality in COVID-19 ( 42 45 ). IL-27 also has potent antiviral effects against influenza, hepatitis B and C viruses, human immunodeficiency virus and others, by stimulating IFNγ production by CD8+ T cells and modulating innate responses ( 46 ). Marked elevation of IL-27 was reported in a single case of mRNA-1273 COVID-19 vaccine-related myocarditis, with more moderate increases in IL-27 in recently vaccinated control individuals (incidentally, inflammasome activation was also implicated in the vaccine-related myocarditis) ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-27 is an anti-inflammatory cytokine that activates Th1 cells and natural killer cells, inhibits Th2 and Th17 cells, and stimulates release of IL-10 by T cells, and has been reported as a reliable predictor of adverse outcomes and mortality in COVID-19 ( 42 45 ). IL-27 also has potent antiviral effects against influenza, hepatitis B and C viruses, human immunodeficiency virus and others, by stimulating IFNγ production by CD8+ T cells and modulating innate responses ( 46 ). Marked elevation of IL-27 was reported in a single case of mRNA-1273 COVID-19 vaccine-related myocarditis, with more moderate increases in IL-27 in recently vaccinated control individuals (incidentally, inflammasome activation was also implicated in the vaccine-related myocarditis) ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…stimulating IFNg production by CD8+ T cells and modulating innate responses (46). Marked elevation of IL-27 was reported in a single case of mRNA-1273 COVID-19 vaccine-related myocarditis, with more moderate increases in IL-27 in recently vaccinated control individuals (incidentally, inflammasome activation was also implicated in the vaccine-related myocarditis) (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, HF2927 differentiation state also influenced p53 transcriptional specificity, as 23 and 26 p53 target genes were significantly upregulated in response to TMZ exclusively in CSCs or SDCs, respectively (Table 2). In contrast, interleukin-27 (IL-27) mediated signaling pathway was enriched in HF2303 SDC in response to TMZ (Fig 8A ), based on the upregulation of Myxovirus resistance dynamin like GTPase 1 (MX1), 2' 5' oligoadenylate synthetase 1 (OAS1) and OAS2, all of which are members of the IRDS [63], underlining the cooperation between IL-27 and IFN signaling previously described [66] in response to DNA damage. To identify other components of IFN signaling in GBMs, we identified 100 genes with expression highly correlated to OAS1 (Spearman's r > 0.55; q value < 5.0E-12) in the TCGA GBM data set (CBIOPortal [67], accessed on 01/19/24).…”
Section: Transcriptional Reprogramming In Response To Csc Differentia...mentioning
confidence: 74%
“…In vitro and in vivo evidence have demonstrated that IL-27 directly enhances IFN production in response to viral infections in various cell types ( 34 , 35 , 44 , 71 , 72 ). Therefore, the potent antiviral activity associated with IL-27 has been attributed to its increased IFN production, which has various antiviral effects.…”
Section: Resultsmentioning
confidence: 99%